Źródło nienawiści - Warzocha, Mikołaj (Kortowski Przegląd Prawniczy, 2021)
This paper examines hatred from a psychological, psychiatric and neurobiological point of view. Hatred from a psychological and psychiatric has been analyzed over the years by well-known scientists. The neurobiological roots of hatred on the other hand are just beginning to be researched, leaving a lot to be discovered on the matter.